Student's Perspective on Pronunciation Using YouTube during Covid-19 Pandemic - Sita Larasati; Abidin Pammu; Nasmilah Nasmilah (Hasanuddin University, 2023)
Pronunciation is one of the English language components that play an important role in creating effective communication. The symbol of sounds is expressed by the arrangement of words (vocabulary) and structures of the sentence (grammar). Besides, pronunciation stands up as an aspect of setting the system of sounds so that the production of vocabulary and grammar are used correctly in oral communication. This study discusses students’ perspectives on the pronunciation of using YouTube during the COVID-19 pandemic. The type of research is descriptive quantitative research. The population in this study was fifth-semester English education students at A class Cokroaminoto Palopo University. The data collection techniques used questionnaire distribution by Google form. The purpose of this study was to determine students’ perspectives of the learning process in phonetics and phonology courses by using YouTube as the learning media. The results of this research indicate that students’ perspectives on pronunciation using YouTube during the COVID-19 pandemic were positive responses. It is supported by students‟ answers where the average percentage of strongly agree in positive response is 34% and agree in positive response is 50%.